Analysis of Electrical Grounding Standards: NBR 16527:2016 e 157751:2013 (2022)
The Study Commission EC 003:102:001 has as its scope to elaborate standards for grounding systems involving specification, definition of materials and measurement parameters, in electric power, generation, transmission, distribution, telephony and data installations and is subordinate ABNT/CB-003 and the Brazilian Committee for Electricity, Electronics, Lighting and Telecommunications (Cobei). The evolution of generation systems, especially in the area of alternative energy, with large wind farms and photovoltaic generation, requires new standards to be established. The interconnection of these systems to substations and to the power supply of the distribution system raises the need for new concepts to be studied.